The effect of blood flow restriction training on core muscle strength and pain in male collegiate athletes with chronic non-specific low back pain - Liu, Yixuan; Liu, Jiahuan; Liu, Min; Wang, Minzhuo (Frontiers in Public Health, 2025)
ObjectiveThe objective of this study is to compare the effectiveness of low-load blood flow restriction training (LL-BFRT) to heavy-load resistance training (HL-RT) in male collegiate athletes with chronic non-specific low back pain (CNLBP).MethodsTwenty-six participants were randomly assigned to LL-BFRT (n = 13) or HL-RT (n = 13). All participants supervised exercises (deep-squat, lateral pull-down, bench-press and machine seated crunch) cycled 4 times per week for 4 weeks (16 sessions). LL-BFRT was done at 30% 1-repetition maximum (1RM) with 70% arterial occlusion pressure (AOP). HL-RT was done at 70% 1-RM. The outcomes were isokinetic core strength, isometric core endurance, pain intensity, and lumbar function disability level, measured at baseline and 4 weeks. Intra-group differences were evaluated using t-tests.ResultsPain intensity and function disability level in LL-BFRT had extremely significant improvement at 4 weeks (p < 0.001, ES = 1.44–1.84). Participants in LL-BFRT and HL-RT showed significant differences in core extensors peak torque-body weight ratio (PT/BW) at isokinetic 120°/s and 30°/s, respectively (LL-BFRT: p = 0.045, ES = 0.62; HL-RT: p = 0.013, ES = 0.81). Isometric core extensor endurance was significantly increased in both groups (LL-BFRT: p = 0.016, ES = 0.78; HL-RT: p = 0.011, ES = 0.83).ConclusionFour weeks of LL-BFRT significantly reduced pain and functional disability while inducing similar strength gains as HL-RT in male collegiate athletes with CNLBP. Thereby, BFRT may qualify as a valuable training strategy for people with physical limitations.